PUM applications and VMDFS file structure: amortised analysis and evaluation. (5th April 2010) - Bagchi, Susmit
The high-end mobile devices, equipped with 3G and higher mobile communication interfaces, have established the ubiquitous computing platform to support a set of mobile applications. The personalised ubiquitous multimedia (PUM) is a promising class of ubiquitous multimedia applications. The PUM applications advocate access to multimedia contents anytime and anywhere needing support from the specialised file systems. The existing distributed and mobile file systems are not adequately suitable to support such applications handling the challenges offered by mobile computing paradigm. This paper briefly introduces the environments of PUM applications along with the file system structure of virtual memory based mobile distributed file system (VMDFS) in view of supporting the PUM applications. The amortised analysis of the VMDFS implementation models is described in mathematical constructs considering the combinations of different pre-fetch models and network models. A set of properties regarding the VMDFS performance is hypothesised through the analysis. The experimental evaluations of VMDFS implementation models validate the hypothesised properties.